Evaluación de la eficiencia de la polinización mecánica en kiwi (Actinidia chinensis var. deliciosa cv. Hayward) - David, Maria Angela; Yommi, Alejandra Karina; Murillo, Natalia Lorena (Asociación Argentina de Horticultura, 2025)
Poster y resumen